Meedium engineering of haloalkane dehalogenase catalysis: Effect of water-miscible organic solvents - Štěpánková, Veronika (2008)
Enzymes represent a potential alternative to chemical synthesis due to their high selectivities and rapid catalysis under ambient reaction conditions. Nevertheless, synthetic chemists have been reluctant to employ enzymes as catalysts, because it was believed that enzymes are only active in aqueous media. Unfortunately, most organic compounds are water insoluble. The realization that enzymes can work and sometimes even improve their substrate specificity, enantioselectivity or stability in the organic media, has changed the prospects of employing enzymes in organic synthesis and industrial bioconversions. This approach, called „medium engineering“, can be also exploited as an alternative to protein engineering. Recently, the use of enzymes in all sorts of non-conventional media, such as organic solvents, supercritical fluids or ionic liquids has been one of the most exciting facets of enzymology. Little information is available on the mechanism of action of organic solvents on enzyme a.